Investigating the hydrogen embrittlement resistance of 3D printed inconel 718 - Lai, Yanfang (Nanyang Technological University, 2022)
Inconel 718 is a Nickel-based (Ni-based) superalloy that is widely used in the aerospace industry whereby it is primarily utilized in production of aircraft engines’ crucial parts such as blades, sheets, and discs. Inconel 718 employed in rocket engines and cryogenic applications due to its outstanding toughness at low temperatures. Inconel 718 produced by Selective Laser Melting (SLM) whereby SLM is a form of additive manufacturing (AM), has gained interest due to the flexibility of manufacturing complex parts. Inconel 718 being an FCC alloy is known to offer good resistance to hydrogen embrittlement. However, there is only limited research concerning the hydrogen embrittlement resistance of Inconel 718 produced by additive manufacturing technique. In this project, SLM fabricated Inconel 718 with 2 different laser parameters was used to study the differences in mechanical properties after hydrogen charging. Further, the two alloys from distinct laser parameters were heat treated to various solution temperature to vary strengthening precipitates size and volume fraction. Effect of hydrogen charging on heat treated Inconel 718 was also studied. The results show that hydrogen charging decreases the elongation to failure of as-printed specimens of both laser parameters. It is shown that the mechanical properties of Inconel 718 such as Yield Strength (YS), Ultimate Tensile Strength (UTS) have significant improvement after undergoing heat treatment processes. However, embrittlement was also observed in heat treated versions. Analysis of fractograph showed embrittlement at the edges of the samples where hydrogen penetration was most effective. Thinner depth of brittle zone shows promising results in using AM Inconel 718 in applications with hydrogen exposure.